Video Art. The First Fifty Years. - London, Barbara (Londen : Phaidon Press ltd, 2020)
Korot, Beryl ; Lucier, Mary ; Hall, David ; Matsumoto, Toshio ; Nauman, Bruce ; Rosler, Martha ; Wegman, William ; Paik, Nam June ; Acconci, Vito ; Vasulka, Steina ; Campus, Peter ; Export, Valie ; Fox, Terry ; Ant Farm ; Jonas, Joan ; Nomura, Hitoshi ; Tanikawa, Shuntaro ; The Residents ; Anderson, Laurie ; Viola, Bill ; Doney, Juan ; Hill, Gary ; Birnbaum, Dara ; Coleman, James ; Kuchar, George ; Oursler, Tony ; Rist, Pipilotti ; Donegan, Cheryl ; Lucas, Kristin ; July, Miranda ; Kentridge, William ; Kuntzel, Thierry ; Mrker, Chris ; Barry, Judith ; Odenbach, Marcel ; Douglas, Stan ; Type, Dumb ; Furuhashi, Teiji ; Melhus, Bjorn ; Scher, Julia ; Friedman, Roberta ; Weinern, Grahame ; Hoberman, Perry ; Beckman, Ericka ; Campbell, Jim ; Arcangel, Cory ; Napier, mark ; Simon, John ; London, Barbara ; Gonxin, Wang ; Peili, Zhang ; Mengbo, Feng ; Fudong, Yang ; Neshat, Shirin ; Malani, Nalini ; Huyghe, Pierre ; reihana, Lisa ; Akomfrah, John ; Kjartansson, Ragnar ; Perry, Sondra ; Cheng, Ian ; Joseph, Kahlil ; Ping, Wong
boek